Sustainable Development and the Consumer: Exploring the Role of Carbon Labelling in Retail Supply Chains. (4th December 2013) - Hornibrook, Sue; May, Claire; Fearne, Andrew
ABSTRACT This empirical article contributes to the sustainable development debate by examining consumer responses to carbon labels within a real world context. Given the limitations of methodologies that use self‐reported or intended measures of purchasing behaviour, we use the loyalty card data of the largest supermarket retailer in the UK to measure the impact of carbon labels on sales by different consumer segments. The data show that the trial of carbon labels on supermarket own brand products has had no discernible impact on shifting demand to lower carbon products. In order to explore possible reasons for lack of impact, nine focus groups were held using purposive sampling by retailer consumer segments to allow an exploration of awareness, understanding and use of carbon labels. The findings from the focus groups identified possible reasons for this lack of impact: lack of awareness and understanding of carbon labelling; constraining or facilitating social and cultural influences; and the heterogeneous nature of consumers. As a result, a number of implications for stakeholders are discussed. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment.